On some numerical methods for solving the 1-D Saint-Venant equations of general flow regime. Part 2: Verification and application - Hanh, Nguyen Van; Diep, Nguyen Van; Can, Ngo Huy (Vietnam Journal of Mechanics, 2003)
In the Part 1 of this paper [1], some numerical methods for solving the 1-D Saint-Venant equations of general flow regime have been described. This Part of the paper presents the results of verification by various test problems, covering all of three flow regimes: sub-, trans-, and super-critical. The results show that the mixed approach (between pointwise and upwind) for source terms is better than the pointwise one and any mathematical transformation of source terms must be careful, since that can lead to nonphysical solutions. The Roe’s approximation with the mixed technique for the source terms is used for a preliminary evaluation of the Son La - Hoa Binh dambreak problem